Why genomics will not revolutionise public health (Italian Journal of Public Health, 2006)
The integration of genome-based information into public health is a challenging task. In this context, someemphasise a supposed fundamental difference of genome-based information compared to other healthinformation. This view is contradicted by the author by arguing that genome-based information is determinedby characteristics which also apply to other non-genome-based health information. Rather genome-basedinformation integrates itself into the range of personal health information. Genome-based informationdeserves no “status apart” just because it was gained with the help of molecular diagnostic techniques. Thusthere will be no revolution in public health, rather it can be discussed how genome-based information could beutilised to be part of public health approaches making public health more target-oriented and efficient.
Keywords: public health genomics; genome-based information; exceptionalism; scientific revolutions; discrimination